2020
DOI: 10.1021/acs.analchem.0c01828
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Temperature-Dependent H/D Exchange Mass Spectrometry Experiments

Abstract: H/D exchange (HDX) mass spectrometry (MS) is a widely used technique for interrogating protein structure and dynamics. Backbone HDX is mediated by opening/closing (unfolding/refolding) fluctuations. In traditional HDX–MS, proteins are incubated in D2O as a function of time at constant temperature (T). There is an urgent need to complement this traditional approach with experiments that probe proteins in a T-dependent fashion, e.g., for assessing the stability of therapeutic antibodies. A key problem with such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…Given that ANGPTL4 binds to the same interface on free LPL and LPL•GPIHBP1 complexes, why does ANGPTL4 binding at 25°C trigger irreversible unfolding only in unbound LPL (and not in GPIHBP1-bound LPL)? A possible explanation rests in the observation that local fluctuations in protein conformations dominate at temperatures well below the melting temperature (T m ), whereas global fluctuations (unfolding/refolding) are predominant at temperatures closer to T m (39). We speculated that differences in T m of LPL and LPL•GPIHBP1 complexes could explain different susceptibilities to ANGPTL4-catalyzed LPL unfolding.…”
Section: Resultsmentioning
confidence: 98%
“…Given that ANGPTL4 binds to the same interface on free LPL and LPL•GPIHBP1 complexes, why does ANGPTL4 binding at 25°C trigger irreversible unfolding only in unbound LPL (and not in GPIHBP1-bound LPL)? A possible explanation rests in the observation that local fluctuations in protein conformations dominate at temperatures well below the melting temperature (T m ), whereas global fluctuations (unfolding/refolding) are predominant at temperatures closer to T m (39). We speculated that differences in T m of LPL and LPL•GPIHBP1 complexes could explain different susceptibilities to ANGPTL4-catalyzed LPL unfolding.…”
Section: Resultsmentioning
confidence: 98%
“…Another report 123 showed that by careful choice of what will be processed, namely, elimination of data that is unlikely to produce any processed results, overall analysis time can be sped up. It was shown that one can extract information from the isotope distribution pattern rather than from an entire uptake time course, 124 and a careful and systematic study 125 of the temperature-dependent factors in HDX MS experiments provided valuable examples and tools for studies of proteins over a wide temperature range.…”
Section: ■ Methods Development: Pre-lcmentioning
confidence: 99%
“…We tested this approach on the unstructured peptide standard bradykinin and the intrinsically disordered aSyn. We hope that this new method, when used with scrutiny, will expand the types of differential HDX-MS experiments that can be done, as at present, it is rare to see comparisons between factors that affect the intrinsic rate (such as pH, temperature, ionic strength) 31,46 .…”
Section: Discussionmentioning
confidence: 99%